Online Teaching and Learning Within the Context Of Covid-19: Exploring the Perceptions of Postgraduate Mathematics Education Students - Jayaluxmi Naidoo; Asheena Singh-Pillay (Department of Mathematics Education University of Muhammadiyah Malang, 2021)
The COVID-19 pandemic has resulted in education institutions using online pedagogy instead of face to face pedagogy to limit the virus’s spread. In this qualitative, interpretive case study, forty-seven mathematics education postgraduate students’ perceptions of online teaching and learning during the COVID-19 pandemic era are explored. The participants were purposively selected from one university in South Africa. The theoretical lens of Virtual Communities of Practice was used to generate data via three interactive online discussion forums. All data were analysed thematically, and the results reveal that the participants perceived strengths and challenges to online teaching and learning within the ambits of COVID-19. This study concludes with suggestions and implications for online teaching and learning for universities in developing countries.